Pre-slaughter cattle management in Brazil: Animal welfare and meat quality - Smaniotto, Bruna Domeneghetti [UNESP]; Lala, Bruno [UNESP] (My University, 2018)
The opening of new market niches for Brazil after the sanitaryrelated events that took place during the 1990s and involved herds from large exporting countries, has boosted participation of Brazil in the international beef trade. Consequently, it was necessary for the country to meet the requirements imposed by the import markets on the quality of the final product, health aspects and animal welfare standards. Given that the national cattle population as a whole has genetic characteristics of the Nellore cattle, which are more reactive than those of the Bos taurus species, it is essential to carry out the steps that make up the pre-slaughter management process so that it fits better with the characteristics of production scenario, in order to reduce the unnecessary stress that results in greater occurrence of bruising, metabolic depletion and the DFD (dark, firm and dry) effect in meat, which result in direct and indirect losses for all parties involved in the productive chain. The negative effects generated by the bruises are the result of the high final pH of the meat and lower yield of the carcass and cuts due to the need to remove and discard the affected tissues, mostly located in the most valued and widely marketed parts of the carcass, like tenderloin, filet and rump. Research carried out in the states with the greatest participation in the production of Brazilian beef reported a high occurrence of bruises in the carcasses, which is an evidence of the fact that there are some flaws in the procedures applied during the pre-slaughter process and that there is still a gap in the knowledge of rational management process that would be adequate for these species of cattle. Training and awareness of those who are involved in the beef production chain regarding the importance of pre-slaughter management in animal welfare, the quality of the final product and as preventive factor against production losses should be carried out continuously. Currently, various initiatives are being developed in Brazil in order to warrant a higher level of welfare in cattle, such as those developed by Ministry of Agriculture, Livestock and Food Supply (MAPA), Good Agricultural Practices Program promoted by the Brazilian Agricultural Research Corporation (EMBRAPA) and STEPS-Humanitarian Slaughter, developed by WSPA-World Society for Animal Protection, so that everyone involved in pre-slaughter management could be made aware of and trained according to the needs and behaviors of these animals, developing production and management techniques that, in addition to serving economic interests, would propose greater welfare, less occurrence of DFD meat and increased profitability of the whole sector.
Keywords: Management; Meat; Nellore; Quality; Welfare